Study of wall re-deposition on DC-grounded ITER-relevant mirrors with RF plasma in a first mirror unit. (22nd October 2021) - Soni, Kunal; Steiner, Roland; Antunes, Rodrigo; Moser, Lucas; Shigin, Pavel; Reichle, Roger; Marot, Laurent; Meyer, Ernst
Abstract: In ITER, several first mirrors (FMs) are expected to be DC-grounded with the water cooling lines being implemented as a quarter wavelength ( λ /4) RF-filter. DC-grounding of the FMs can significantly increase the plasma potential V p, which could trigger an increased wall sputtering and associated re-deposition on the FMs during plasma cleaning. To understand the scope of this impact, helium discharges were excited with DC-grounded FMs in an ITER-sized mock-up of a first mirror unit (FMU) using wall materials with different sputtering energy thresholds ( E th ). Additionally, a part of the FM was electrically isolated from the RF to study its impact on the erosion/re-deposition properties on the surface. The E th of the wall materials, as well as its native oxide layers, had a significant influence on the re-deposition observed on the FMs. With high E th where walls were unsputtered, both the DC-grounded and electrically isolated parts of the FM were free of deposits. However, with low E th where the walls were sputtered, there was a net wall re-deposition on the DC-grounded parts of the FM, while electrically isolated parts were still relatively clean. Further, to study the impact of floating wall components, Cu walls in the FMU were isolated from the ground. Here the walls developed a floating potential V f and the ion energy at the walls was lowered to e ( V p − V f ). The floating walls, in this case, were relatively unsputtered and the FMs experienced a net cleaning with total reflectivity of the mirror preserved at pristine mirror levels. This work shows that electrically isolating the FM as well as the wall surface minimizes wall re-deposition in presence of λ /4 filter and therefore are promising techniques for effective FM cleaning in ITER.